Kojic Acid Showed Consistent Inhibitory Activity on Tyrosinase from Mushroom and in Cultured B16F10 Cells Compared with Arbutins - Wei Wang; Ying Gao; Weiwei Wang; Jianyong Zhang; Junfeng Yin; Ting Le; Jinjin Xue; Ulrich H. Engelhardt; Heyuan Jiang (Antioxidants, 2022)
Kojic acid, β-arbutin, α-arbutin, and deoxyarbutin have been reported as tyrosinase inhibitors in many articles, but some contradictions exist in their differing results. In order to provide some explanations for these contradictions and to find the most suitable compound as a positive control for screening potential tyrosinase inhibitors, the activity and inhibition type of the aforementioned compounds on monophenolase and diphenolase of mushroom tyrosinase (MTYR) were studied. Their effects on B16F10 cells melanin content, tyrosinase (BTYR) activity, and cell viability were also exposed. Results indicated that α-arbutin competitively inhibited monophenolase activity, whereas they uncompetitively activated diphenolase activity of MTYR. β-arbutin noncompetitively and competitively inhibited monophenolase activity at high molarity (4000 µM) and moderate molarity (250–1000 µM) respectively, whereas it activated the diphenolase activity of MTYR. Deoxyarbutin competitively inhibited diphenolase activity, but could not inhibit monophenolase activity and only extended the lag time. Kojic acid competitively inhibited monophenolase activity and competitive–noncompetitive mixed-type inhibited diphenolase activity of MTYR. In a cellular experiment, deoxyarbutin effectively inhibited BTYR activity and reduced melanin content, but it also potently decreased cell viability. α-arbutin and β-arbutin dose-dependently inhibited BTYR activity, reduced melanin content, and increased cell viability. Kojic acid did not affect cell viability at 43.8–700 µM, but inhibited BTYR activity and reduced melanin content in a dose-dependent manner. Therefore, kojic acid was considered as the most suitable positive control among these four compounds, because it could inhibit both monophenolase and diphenolase activity of MTYR and reduce intercellular melanin content by inhibiting BTYR activity without cytotoxicity. Some explanations for the contradictions in the reported articles were provided.